Neuroendocrine-Immune Homeostasis Disruption in Livestock: Molecular Mechanisms, Health Consequences, and Mitigation Strategies A Systematic Literature Review - Sabrina Putri Setiawan; Zalfa Hervianuri; Amelia Fildza Ramadhani; Adit Rizki Sudrajat; Afridha Laily Alindra (BIOCHEPHY: Journal of Science Education, 2026)
Livestock are routinely exposed to environmental, nutritional, managerial, and infectious stressors that challenge the neuroendocrine and immune systems. Dysregulation of this integrated axis is increasingly recognised as a principal driver of reduced health resilience and productive performance. This systematic literature review characterised the molecular mechanisms underlying neuroendocrine–immune homeostasis in livestock, identified major disruption categories triggered by stressor exposure, and synthesised evidence-based mitigation strategies. Forty-one peer-reviewed articles from 2020–2026 were retrieved from Scopus, Web of Science, and Google Scholar and analysed through data reduction, display, and conclusion drawing. Findings indicate that chronic HPA axis over-activation triggers six inter-related disturbances: periparturient immunosuppression, Th1/Th2 imbalance, reproductive hormone dysregulation, pro-inflammatory cytokine dysregulation, heat-stress-induced endocrine disruption, and negative energy balance collectively heightening susceptibility to mastitis and metritis while suppressing reproductive efficiency and growth. Effective mitigation requires adaptive housing, precision nutrition, and evidence-based welfare practices to sustain livestock productivity in tropical systems.